Leadership Styles and Job Performance with EducationalTrainings as Mediator among Employees in the Public andPrivate Educational Sectors in Shanghai, China - Xiaoli, Wen; Tahir, Suhaidah Binti (South Asian Journal of Social Sciences and Humanities, 2024)
Background: Leadership styles have gained significance for driving the level of efficiency and productivity among the staff, enhancing their overall performance. The present study is designed to investigate the impact of distributed leadership, transformational leadership, and transactional leadership on the job performance of employees in the public and private educational sectors in Shanghai, China. In addition, the present study focuses on exploring whether educational training mediates the relationship between these leadership styles and the job performance of employees. Methods: The present study adopted a quantitative survey based approach to collect data from a diverse population of employees from China’s public and private educational sectors and analyses the data through implementing the partial least squares structural equation modeling (PLS-SEM) approach. Findings: The outcomes of the study validated the positive and significant influence of leadership styles on job performance. The study showed that transformational, transactional, and distributed leadership enhances the job performance of employees in educational institutions. Furthermore, the study did not find empirical evidence to support the mediating role of educational training. Conclusion and Implications: The study established the pivotal role of leadership styles in enhancing employee performance in the context of educational sectors of China. The findings hold theoretical value by extending the current literature on leadership. In addition, the findings can inform policymakers, managers, and educators to develop effective strategies and policies that support a positive and conducive workplace environment to enhance the job market. Focus should be given to leadership development for educational leaders to meet the needs of organizations.